Introduction to statistical quality control - Montgomery, Douglas C. (Hoboken, NJ : John Wiley & Sons, Inc., 2020)
"This book is about the use of modern statistical methods for qualit y control and improvement. It provides comprehensive coverage of the su bject from basic principles to state-of-the-art concepts. and applicati ons. The objective is to give the reader a sound understanding of the p rinciples and the basis for applying them in a variety of situations. A lthough statistical techniques are emphasized. throughout, the book has a strong engineering and management orientation. Extensive knowledge. of statistics is not a prerequisite for using this book. Readers whose background includes a basic course in statistical methods will find muc h of the material in this book easily accessible"--
Includes bibliographical references and index.
Keywords: Quality control -- Statistical methods; Process control -- Statistical methods